Robust domain variants and ferroelectric property in epitaxial BiFeO3 films. (30th December 2020) - Qiao, Xiaojun; Geng, Wenping; Meng, Jianwei; Sun, Yao; Bi, Kaixi; Yang, Yun; Yu, Junbin; He, Jian; Chou, Xiujian
Abstract: Lead-free ferroelectric thin films have great potential for electric devices owing to the dramatically expanding information epoch. Exploring the domain engineering and temperature stability of ferroelectric films are still urgent since these polarization dipoles are sensitive to external effects. In this work, the temperature dependence of domain dynamic and local piezoelectric response were investigated in epitaxial BiFeO3 (BFO) thin films prepared by pulse leaser deposition (PLD) technology, which exhibiting well-defined polarization switchable intrinsic property. Regarding to temperature endurance, domain variants remain quite stable state regarding to both the vertical and lateral direction, which is in consistent with the free-energy minimum competition theory. Besides, the piezoelectric response along vertical and lateral direction exhibit good temperature endurance. This work demonstrates thin films with rather stable ferroelectric states, which show not only exploration on domain dynamic corresponding to temperature influence, but also promising potential application in electrical storage devices especially working under high temperature.